Влияние зарубежных СМИ на информационное пространство Кыргызстана - Алишер, Саипов (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The Author discusses selected issues concerning the altered functions of mass media in the course of political transformation in Kirghizia.